A prototype of a mobile car rental system - Mon, Chit Su; Tee, Tan Khee; Amir Hussin, Amir Aatieff (Institute of Physics Publishing, 2020)
The project aimed to propose a prototype of a mobile car rental system that is secured and enabled users to reserve the vehicle they wanted. The proposed mobile car rental system has been replaced by the traditional way of renting vehicles. General functions such as adding, editing and removing information will be added to the mobile app. Other features such as login, direct call and send email, direct location, check vehicle availability, check vehicle reservation, and so on will be added to the mobile app. The app also allowed users to view the rental car available, make payment for the rental car using a credit card that ensures that users do not have to be physically present at the rental company just to see what rental car they want to rent. Instead, users could browse the car rental list through the Mobile Car Rental System, no matter how many times, and then decide which car to choose and proceed for payment process. On the other hand, the app also allowed admin to have full control over the app where admin could add, edit, and remove any car information at any time.